Operating-System Design and Its Implications for Victims of Family Violence: The Comparative Threat of Smart Phone Spyware for Android Versus iPhone Users. (May 2021) - Harkin, Diarmaid; Molnar, Adam
Spyware products sold to general consumer audiences are a greater threat to those who own Android devices than those who own iPhones. This is a consequence of the Android operating system being more permissive of software functionality, allowing third-party developers greater latitude to build programs of less-restrained capability. Such risks, however, are disproportionately carried by victims of family violence who are significantly threatened by the rise of spyware. This article reflects on the connections between coding choices and personal security risks, and the implications for responding to the use of spyware in the context of family violence.